Efficacy of extracorporeal shockwave lithotripsy with furosemide and hydration in renal stone management: A randomised controlled trial. Issue 4 (2nd October 2019) - Sohu, Safiullah; Soomro, Munawar Hussain; Mangrio, Riaz Hussain; Shaikh, Arif Ali; Mirani, Azizullah; Chand, Khoob; Jalbani, Malik Hussain
ABSTRACT: Objective : To assess the effect of diuretics (furosemide) administered before extracorporeal shockwave lithotripsy (ESWL) followed by continuous infusion of 0.9% NaCl during the ESWL in patients with renal stones. Patients and methods : A tertiary care teaching hospital-based prospective randomised controlled trial was conducted from July 2015 to June 2017, including 714 patients who underwent ESWL. The patients were randomised in two groups: in Group-A, patients received 40 mg furosemide 30 min before each ESWL session and 1000 mL 0.9% NaCl intravenous hydration during the procedure. In Group-B, the patients only received 0.9% NaCl. All patients were followed-up every 2 weeks for 3 months with X-ray and ultrasonography of the kidney, ureter and bladder. Patients without a radio-opaque stone at follow-up were classified as successes. Results : After 2 months, the stone-free rate (SFR) was much higher in Group-A, at 77.0% vs 65.3% ( P < 0.001). Further, for patients aged ≤40 years, the SFR was significantly higher in Group-A than Group-B, at 89.2% vs 71.4% ( P < 0.001). The mean (SD) age of the patients was 34.4 (8.23) years. Amongst them, 441 (61.8%) were male and 273 (38.2%) were female. The mean (SD) stone size was 1.42 (0.21) cm in Group-A and 1.40 (0.20) cm in Group-B. Conclusion : We conclude that the efficacy of diuretics (furosemide) along with hydration is superior to hydration alone during ESWL for renal stone clearance. Abbreviations : BMI: body mass index; KUB: kidney, ureter and bladder; OPD: Outpatient Department; ESWL: extracorporeal shockwave lithotripsy; SFR, stone-free rate.